Plastic Show. - Pissarro, Joachim; Jattiot, Antoinette; Cavers, Ailsa (London : Almine Rech Gallery, 2017)
Corse, Mary ; Irwin, Robert ; Kauffman, Craig ; McCracken, John ; Valentine, DeWain
Plastic Show, Organized by DeWain Valentine, Almine Rech Gallery, London, February 9 - March 25, 2017
boek